Expressive Brand Relationship, Brand Love, and Brand Loyalty for Tablet PCs: Building a Sustainable Brand - Zhang, Shikun; Peng, Michael Yao-Ping; Peng, Yaoping; Zhang, Yuan; Ren, Guoying; Chen, Chun-Chun (Frontiers in Psychology, 2020)
Due to the findings are confounded that the relations between brand relationship and brand loyalty, drawing on the relationship marketing theory. This study collected from three metropolitan customers who used tablet PC. We get 383 valid samples, valid response rate is 89%. Data analysis was performed using structural equation modelling to test the proposed model. The results indicated that expressive brand relationship significant predicators of brand trust and brand loyalty. Brand trust has positive influence brand love. Brand conscious and brand love has influence attitudinal and behavioral loyalty. Expressive brand relationship through two indirect mediating affects which brand trust and brand love influence brand loyalty. Finally, these results suggest managerial implications and the direction of future researches.